2011
DOI: 10.1136/bmjqs.2010.046227
|View full text |Cite
|
Sign up to set email alerts
|

Problems and promises of innovation: why healthcare needs to rethink its love/hate relationship with the new

Abstract: Innovation is often regarded as uniformly positive. This paper shows that the role of innovation in quality improvement is more complicated. The authors identify three known paradoxes of innovation in healthcare. First, some innovations diffuse rapidly, yet are of unproven value or limited value, or pose risks, while other innovations that could potentially deliver benefits to patients remain slow to achieve uptake. Second, participatory, cooperative approaches may be the best way of achieving sustainable, pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 30 publications
0
83
1
1
Order By: Relevance
“…[33][34][35][36] Conversely, some recent work has also described the potential for innovations with high degrees of intuitive appeal to diffuse rapidly into clinical practice, even if definitive proof of efficacy is lacking. 37,38 In this present study, we observed a rapid adoption of preoperative β-blocker treatment after initial reports that suggested clinical efficacy. 4,5 Notably, this trend in clinicians' behavior occurred before similar recommendations by perioperative practice guidelines.…”
Section: Discussionmentioning
confidence: 55%
“…[33][34][35][36] Conversely, some recent work has also described the potential for innovations with high degrees of intuitive appeal to diffuse rapidly into clinical practice, even if definitive proof of efficacy is lacking. 37,38 In this present study, we observed a rapid adoption of preoperative β-blocker treatment after initial reports that suggested clinical efficacy. 4,5 Notably, this trend in clinicians' behavior occurred before similar recommendations by perioperative practice guidelines.…”
Section: Discussionmentioning
confidence: 55%
“…Normalisation process theory [2] Sociology Practices are determined by perceived coherence of intervention, cognitive participation of target group, collective action, and reflexive monitoring. Organisational readiness theory [3] Organisational science…”
Section: Key Ideasmentioning
confidence: 99%
“…Investments in basic and clinical research remain wasted if effective clinical or preventive interventions, medical devices or organizational models are not applied in practice. On the other hand, resistance to change is appropriate if it helps to preserve good practices [3].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, it is a critical determinant and means (perhaps the most signifi cant) of improving safety in the long term. Innovation may also introduces new risks as well as resolving old ones particularly in the short term during the period of transition and disruption (Dixon-Woods et al 2011 ). Safety may be degraded in the short term due to rapid diffusion of insuffi ciently tested new methods and uncontrolled individual experimentation.…”
Section: Innovationmentioning
confidence: 99%